School-based cyberbullying prevention in the peer ecology: social norms, bystander behaviour, and school connectedness - Berghauer-Olasz Emőke; Бергхауер-Олас Емйовке; Chains Victoria; Lánczi Viktória; Ланці Вікторія (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. This article examines school-based cyberbullying through the lens of the peer ecology. Evidence from 2024 – 2025 shows that incidents persist even where basic online-safety lessons exist, if classroom social norms tacitly tolerate aggression and bystanders expect others to remain passive. Synthesising findings on the roles of descriptive and injunctive norms, the effectiveness of bystanderfocused programmes, and the protective function of school connectedness, we propose a three-lever prevention model: (1) explicit norm work in class that surfaces perceived peer approval, corrects pluralistic ignorance, and co-creates a defending-oriented injunctive norm; (2) rehearsal of defending in realistic digital scenarios that personalise responsibility and lower situational barriers to intervention; and (3) strengthening school connectedness via visible adult follow-up, recognition of prosocial bystander actions, and sustained teacher - student relationship routines. Designed for Ukrainian and wider Central-European contexts (including hybrid learning and limited adult supervision online), the model treats cyberbullying as a relational phenomenon distributed across skills, group processes, and institutional climate. By shifting the target from “what students know” to “what they believe their peers expect,” it increases the likelihood of early supportive bystander action and durable reductions in both perpetration and victimisation.
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: cyberbullying; social norms; bystander behaviour; school connectedness; peer ecology; prevention; adolescent wellbeing